Historical outline of Polish legislation on abortion (from the interwar period to 1997) - Tarnacka, Agata; Tarnacki, Damian (Protection of human life at the prenatal stage of development: Social, medical and legal aspects, 2026)
The subject of this chapter is to present, within the framework of a historical outline, how the legal regulations concerning the permissibility of abortion in Poland evolved in the years 1918–1996. The chapter opens with a dis cussion of the regulations from the inter-war period, the Nazi occupation, and the communist era. This is followed by a detailed discussion of the proposed abortion laws debated in parliament between 1989 and 1997, i.e., the entire path leading to the enactment of the currently binding Act of 7 January 1993 on family planning, protection of the human foetus and the conditions of permissibility of terminating a pregnancy.